TEKNOLOGI PENGEMASAN OLAHAN IKAN BANDENG PADA UKM “ADINDA” DESA GERSIK PUTIH SUMENEP - Putri, R. D.; Hanafi, I.; Wise, N. (Buletin Udayana Mengabdi, 2022)
KWT "Adinda" is a group engaged in the productive economy of cultivation and processing, located in the white sandy village of Gapura sub-district. Problems faced in business management. This is because the packaging is less attractive so that consumer interest is very low. The goal of community service is to improve the economy through the application of packaging and labeling technology and business management, thereby increasing partner income. The material presented was about packaging technology, labeling, types of packaging, the ability of packaging to protect products, and consumer acceptance. The implementation was attended by 10 partner members. The method used is training and mentoring partners. The results of this activity can broaden insights regarding packaging and labeling as well as business management, so that economic income increases.